Product and customer development (general banking & mobile financial services-UCash): a study on United Commercial Bank - Babai, Md. Preyanker Syed (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.